FIDIC green book : a companion to the 2021 Short form of contract - Srensen, Jakob B. (ICE Publishing, 2022)
FIDIC Green Book: A companion to the 2021 Short Form of Contract is a practical guide for anyone involved in preparing, administering, or contributing to the 2021 FIDIC Short Form of Contract (FIDIC Green Book). Designed as a companion for both first-time and more experienced users, the book presents an accessible guide to the 14 clauses of the FIDIC Green Book. Opening chapters introduce international construction contracts, including the entire FIDIC suite of contracts, and definitions of key terms. Chapters in Part 2 give a brief introduction to each of the Clauses and Sub-Clauses in the FIDIC Green Book, and explain how they are interlinked. The final section is a concise practical guide to the use of the FIDIC Conditions, and summarises special provisions discussed in Part 2.